Environmental impacts of an environmental education program through life cycle assessment - Dutra, Ana Carolina; Medeiros, Gerson Araújo de; Gianelli, Bruno Fernando; Paes, Michel Xocaira (Revista Hipótese, 2019)
The potential environmental impacts of the environmental education program of the Division of Rural Prodction, from the São Paulo Zoo Foundation, were estimated through the the life cycle assessment. The software SimaPro 7.3.0, the Ecoinvent database and the Eco-Indicator 99 (H) method were used. The disposal scenario to landfill was responsible from 67% of the total impacts. This result justifies the introduction of composting, which would represent a 37% reduction in environmental impacts.
Keywords: Environmental Management; Zoo; Environmental education; Life cycle inventory